PENERAPAN METODE MODIFIED DISTRIBUTION (MODI) UNTUK OPTIMALISASI BIAYA DISTRIBUSI PRODUK ALAT KESEHATAN - Windu Alfianti; Reni Kurnia; Rizka Oktaviani; Muchammad Fauzi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
The transportation model is the lowest cost plan determination for a distribution process. This research aims to obtain the pattern of distribution of medical device products at PT X so that the costs for the distribution process become more optimal and the needs of product demand to each city can be met. By using Vogel's Approximation Method (VAM) as a viable initial solution and followed by optimization tests to determine the optimal solution with Modified Distribution Method (MODI). The results showed the initial solution of VAM method obtained cost Rp176,645,930 then Modified Distribution Method (MODI) as the optimal solution obtained optimal transportation costs of Rp176,645,210. Based on the results of calculations that have been done shows the results that the distribution of medical devices in PT. X by implementing a transport model can save on distribution costs